Allelopathic Properties of the Species Comprising Communities of Invasive Impatiens spp. and Antioxidant System of Invaders’ Populations - Eugenija Kupcinskiene; Ruta Budreviciute; Vaida Jasionyte; Laura Simanaviciute; Lina Jociene; Edvina Krokaite-Kudakiene; Tomas Rekasius; Vitas Marozas (Diversity)
Globalization has greatly expanded the opportunities for plant species to enter new areas through a wide range of pathways. Elucidating the pathways of spread of alien species and the characteristics of organisms that make them invasive is one of the most pressing problems in ecological sciences. Once established, alien species may have serious implications for communities and vice versa. Allelopathy has been proposed as one of the possible invasion mechanisms of exotic plants. Impatiens parviflora and Impatiens glandulifera are among the widely spread invasive plant species in the Baltic region. The aim of the study was to evaluate the allelopathic effect of invasive Lithuanian Impatiens spp. and their neighboring plants (11 pristine species) using parameters of germination and seedling growth of biotest species Lepidium sativum, and to expand this study by determining the content of phenolic compounds and the radical scavenging activity in the leaf extracts of Lithuanian Impatiens spp. populations (20 of each Impatiens species). Leaf extracts of all species examined had an inhibitory effect on Lepidium sativum germination and morphology of the seedlings. In our study, at all leaf extract concentrations, significantly higher allelopathic potential on radicle growth was characteristic of I. glandulifera compared to native species Alnus glutinosa, Calystegia sepium, and Urtica dioica. At all leaf extract concentrations, I. parviflora showed significantly higher allelopathic potential on radicle growth compared to native species Urtica dioica. Impatiens glandulifera had a higher juglone index than Impatiens parviflora. I. glandulifera also had the highest juglone index compared to all neighboring species studied. The differences between the populations in the content of phenolic compounds, DPPH and ABTS radical scavenging activity were 2.3, 2.2 and 2.7 times for I. glandulifera and 2.6, 5.2 and 2.7 times for I. parviflora. The mean values of total phenolic content, DPPH and ABTS radical scavenging activity of I. glandulifera populations were 2.1, 2.7 and 3.3 times higher than those of I. parviflora populations, respectively. In general, our results about allelopathic potential and phenolics content, as well as free radical scavenging ability, confirm the supreme competitive ability of I. glandulifera compared to both I. parviflora and to the native co-occurring species.